AICCRA Country Scaling Vision: Senegal - Whitbread, Anthony M.; Worou, Nadine; Yessoufou, Adjani Nourou-Dine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
By the end of 2023, AICCRA Senegal aims to reach and have positive impacts on over 300k farmers and value chain players through the delivery of climate informed agro-advisories, building on enhanced climate information services (CIS), and new/improved climate smart agricultural (CSA) packages and technologies. The strategy for this scaling vision uses multiple pathways and is achieved through partnerships with the National Agricultural, Research and Extension Services (NARES) and private sector in Senegal. A conceptual framework for this vision is adapted from the Scan tool following Jacobs et al. (2018).